Criteria for placenta accreta spectrum in the International Federation of Gynaecology and Obstetrics classification, and topographic invasion area are associated with massive hemorrhage in patients with placenta previa. (23rd March 2021) - Ishibashi, Hiroki; Miyamoto, Morikazu; Iwahashi, Hideki; Matsuura, Hiroko; Kakimoto, Soichiro; Sakamoto, Takahiro; Hada, Taira; Takano, Masashi
Abstract: Introduction: Placenta previa with placenta accreta spectrum (PAS) is a life‐threatening disease that results in massive hemorrhage. The clinical and histologic criteria of PAS were adopted according to the International Federation of Gynaecology and Obstetrics (FIGO) classification. We aimed to investigate whether FIGO criteria and topography were associated with maternal complications in patients with placenta previa. Material and methods: Patients with placenta previa who underwent cesarean section at our institution between January 2003 and December 2019 were identified. First, they were divided based on FIGO classification, as follows: Group A, with clinical criteria; Group B, with histologic criteria; and Group C: without clinical or histologic criteria. Next, cases with PAS were classified according to the topographic invasion area, as follows: type 1, upper posterior bladder; type 2, lower posterior bladder; type 3, parametrium; type 4, posterior lower uterine segment. Predictive factors for massive hemorrhage were retrospectively analyzed. Results: Among the 350 patients, 24 (6.9%) were classified as Group A, 16 (4.6%) as Group B and 310 (88.5%) as Group C. Regarding maternal history and hemostatic procedures, there were no significant factors other than hysterectomy ( p < .01) in Groups A and B. The volume of blood loss in both Groups A and B was greater than in Group C ( p < .01). The rates of uterine artery embolization and blood transfusion were higher in Groups A and B than in Group C ( p < .01). In addition, there were no significant factors other than hysterectomy between Groups A and B. In the multivariate analysis for massive hemorrhage, Group A (odds ratio: 2.73, p = .04) and Group B (odds ratio: 12.69, p < .01) were identified as independent predictive factors. In addition, massive hemorrhage was closely related to the lower posterior bladder and parametrial invasion in both Groups A and B. Conclusions: Both clinical and histologic criteria for PAS in the FIGO classification were associated with massive hemorrhage. Diagnosing clinical PAS using the FIGO classification, additional hemostatic procedures might be necessary according to the topographic invasion area.